Long distance travel ‘today’ - Christensen, Linda (Proceedings from the Annual Transport Conference at Aalborg University, 2014)
This paper presents an overview of the Dane’s long distance travel. It is a part of the Drivers and Limits project about long distance travel. Long distance travel is in the project defined as infrequent travel with overnight stay. Danes 15-85 years-old travel in average 5.5 long distance travel per year og which a third is for international destinations, a third is for domestic second homes and a third are other domestic trips. However, 87% of the kilometres are for international destinations and only 4% are for domestic second homes. Travel activity is very uneven distributed with only half of the population having had a journey during the last three month. At the other hand 60% have travelled internationally during the last year and only 2% have never travelled abroad. The paper presents among other things how the travel activity is distributed on travel purpose and mode and how the mode choice depends on travel distance and destination.